Stover biogas potential of corn crops grown under contrasting water availability and nitrogen supply - Erbetta, Elisa; Echarte, Laura; Rodríguez Elizagaray, Consuelo; Depetris, Gustavo; Gabbanelli, Nadia; Echarte, María Mercedes (Elsevier, 2021)
Corn stover is a biogas feedstock capable of enhancing agriculture bioenergy potential. Although the influence of growing conditions on biogas yield of corn stover has been reported, the joint effects of water and nitrogen on biogas production potential have not been addressed. A two year experiment (Exp. 1 and Exp. 2) was conducted in Balcarce, Argentina to assess nitrogen supply effects on stover composition and potential methane yield of corn crops grown under contrasting water regimes. Treatments were a combination of two nitrogen fertilization doses (0 and 120 kg ha−1) and two water regimes (irrigated and rainfed). Biomass composition (mass closure procedure) was determined, a BMP test was carried out and first-order kinetic parameters were obtained. Interactive effects of nitrogen and water on stover composition were found. BMP tests showed that the biogas production rate (k) decreased upon irrigation while its response to nitrogen depended on water availability. Nitrogen supply decreased specific biogas potential (Bmax) independently of water availability. Methane yield increased with nitrogen fertilization under irrigation, while it decreased under rainfed conditions. The observed water and nitrogen supply interactive effects on stover yield, methane yield and biomass conversion efficiency highlights the importance of considering the joint effects of multiple factors when trying to assess the effects of the environment on biomass quality for bioenergy purposes.